Where no one can hear you - Rowney, J. E. (Little Fox Publishing, 2025)
"Sixteen-year-old Amanda Gray's life shatters when what should have been a simple walk home with her best friend Sarah turns into a nightmare. One moment they're picking bluebells in the woods; the next, they're at the mercy of a predator who seems chillingly familiar with his routine. Six weeks later, Amanda wakes in a hospital bed with a slash across her throat, her voice stolen, and no memory of how she escaped. And no one will talk to her about Sarah. And the worst part? Her most crucial memory might be the one she can't speak."--Page [4] of cover